Retinoblastoma (RB) in Saudi Arabia- Retrospective Comparative Review of a Registry - Amir Pirouzian (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2015)
Purpose: Published data regarding retinoblastoma in Saudi Arabia (KSA) is sparse. The study will present comparison of clinical and pathologic features, and evolving patterns of the treatment during 1983-1997 (Early group=EG) to 1998-2012 (Late group=LG) periods from an RB registry representing all Rb cases in KSA.  Methods: This health record review was conducted in 2014. From the RB registry, information about  gender, age, clinical features and stage at presentation; laterality, regional distribution, history, co-morbid diseases, pathologic features, surgical treatment modality and treatment outcomes were collected. Results: The EG and LG group had 343 and 430 Rb patients respectively. The incidence of Rb in 1997 and in 2012 was 0.06 and 0.03 per 1,000 live births in Saudi Arabia respectively. The gender distribution was similar. The median age of presentation was 24 (range 11, 39) months in EG vs. 18 (8, 31) months in LG (p <0.001). Incidence of unilateral Rb was 58% [200/343] in EG vs. 56% [278/485] in LG. Positive family history of Rb was <10% in both groups. However, in EG, 120 (35%) parents were first cousins vs. 124 (27%) in the LG (p=0.12). Leukocoria was the most common presentation [71% (n=255) in EG and 66% (n=343) in LG]. Tumor confined to the eye at presentation was more common in the LG group (67% EG vs. 84% LG). Vitreous seeding was more common in LG [62% (n=302) LG vs 45% (n=156) EG; p<0.001]. In the non-surgical group, photocoagulation rate increased in the LG [23.19% (106) LG vs 3.8 %( n=13) EG; p<0.001]. The rate of chemotherapy increased from 4.1% (n= 14) in EG to 14.2% (n=65) in LG (p <0.001). The rate of external beam radiation decreased [37% (n=125) EG vs. 23.4% (n=107) LG]. The rate of extraocular tumor extension was similar in both groups (53.7% EG vs. 51.6% LG; p<0.001). The rate of full thickness choroidal involvement decreased from 13% (n=35) EG to 7.7 % (n=30) LG, (p =0.04). Optic nerve (ON) involvement in LG decreased to 3.4% (n=22) compared to 9.8 %( n=48) in EG (p <0.001).  Conclusions: Most clinical parameters of Rb remained unchanged over 30 years except an earlier median age of presentation suggesting earlier tumor detection. However, an increasing total number of Rb cases were seen in the last fifteen years. The pathologic features in LG were less advanced. A significant increase in the non-surgical treatment approaches of Rb was noted in the last 15 years.